2018
DOI: 10.1002/jhbp.588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antithrombic therapy on bleeding complications in patients receiving emergency cholecystectomy for acute cholecystitis

Abstract: Background The risk of developing hemorrhagic complications during or after emergency cholecystectomy in patients with antithrombic therapy (ATT) remains uncertain. In this study, we evaluate outcomes in patients with ATT undergoing emergency cholecystectomy and assess the relevance between ATT and perioperative complications including bleeding complications. Methods We retrospectively evaluated 296 patients who were diagnosed as acute cholecystitis and underwent emergency cholecystectomy between 2005 and 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…Regarding the bleeding risks, the safety of preoperative single APT continuation during various types of surgery has been reported [4][5][6][7][8][9][10] . Although some studies including POISE-2 study have reported a slight increase in bleeding risks after non-cardiac surgery in patients with APT continuation [4,5] , most studies have shown that preoperative APT continuation is not associated with significant bleeding complications [6][7][8][9] .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the bleeding risks, the safety of preoperative single APT continuation during various types of surgery has been reported [4][5][6][7][8][9][10] . Although some studies including POISE-2 study have reported a slight increase in bleeding risks after non-cardiac surgery in patients with APT continuation [4,5] , most studies have shown that preoperative APT continuation is not associated with significant bleeding complications [6][7][8][9] .…”
Section: Resultsmentioning
confidence: 99%
“…Research article collection and screening were conducted from January 2019 to February 2019. A total of 8 studies on surgical cholecystectomy (mainly LC), [11][12][13][14][15][16][17][18] 3 studies on PTGBD, [19][20][21] and 1 study on EGBD 5 in patients receiving ATT were selected for data extraction and satisfied our inclusion criteria. As only 1 study on EGBD in patients receiving ATT was retrieved through the search method mentioned above, articles were additionally searched using the keywords "ETGBD" and "EUS-GBD".…”
Section: Study Collectionmentioning
confidence: 99%
“…In the 12 studies that evaluated surgery and gallbladder drainage, patients receiving ATT, including aspirin and/or thienopyridine, were the focus of 3 studies. 12,14,15 Only 1 study evaluated patients receiving anticoagulant therapy with heparin bridging, 11 1 study evaluated patients receiving anticoagulant therapy and/or with coagulopathy, 19 and the other studies 5,13,[16][17][18]20,21 evaluated patients receiving antiplatelet agents and/or anticoagulants during surgery (LC or OC) or internal drainage (PTGBD or EGBD) without discontinuation of ATT (Table 1).…”
Section: Gallbladder Drainage In Patients Receiving Attmentioning
confidence: 99%
See 2 more Smart Citations